Predictors of Non-Invasive Ventilation Failure in Respiratory Intensive Care - Safa M. Wafy; Hassan A. Bayomy; Sahar A. Mohamed; Mostafa K. Ahmed (Egyptian Journal of Critical Care Medicine)
Abstract Introduction Non-invasive ventilation (NIV) is commonly conducted respiratory support in acute respiratoryfailure setting. NIV is used to prevent and lower the need for invasive mechanical ventilation (IMV) to avoid IMV complications; however, still researches are needed to identify the ideal patient for non-invasive ventilation. Our goal to display the factors related to NIV failure in respiratory ICU (RICU). Patients and methods In a consequent patients referred to RICU, Assiut University for respiratory support and management, we recruited patients who had non-invasive ventilation and followed them till success weaning from NIV or fail and needed IMV, all these patients were followed till discharge from the RICU in the period between May 2018 and May 2019; clinical data and laboratory investigations of all patients including sequence arterial blood gas, complete blood count, liver functions tests, kidney function tests, together with non-invasive ventilation setting data were collected and analyzed for identifications of the predictors of worse outcome. Results 150 patients were enrolled in the study, 56 (37.3%) patients had failed NIV while 94 (62.7%) patients had successful NIV. Mean age of patients with successful NIV was 57.40 ± 12.13 years and majority (53.2%) of them was males while mean age of those with failed NIV was 58.25 ±13.44 years and majority (55.4%) of them was females. Restrictive and obstructive lung disease presented in 19 (20.2%) and 75 (79.8%) of patients with successful NIV and presented in 24 (42.9%) and 32 (57.1%) of patients with failed NIV, respectively. Predictors for failed NIV were restrictive lung disease (OR = 1.94, 95%CI = 1.64–5.88; P = 0.04), expiratory positive airway pressure (OR = 1.18,95%CI = 1.08–1.64; P = 0.02), auto trigger (OR = 1.18,95%CI = 1.07–1.58; P = 0.01), and acute physiology and chronic health evaluation II (APACHE-II) (OR = 2.11, 95%CI = 1.07–5.78; P = 0.01) with adjusted R2 was 0.68. Conclusion Physician in respiratory intensive care should be cautious when applying NIV for restrictive pulmonary diseases, type 1 respiratory failure, and also patients have APACHE-II score more than 17.